(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Pervious concrete, which is also known as Porous Concrete, Permeable Concrete, Gap-Graded Concrete, No-Fines Concrete, Enhanced-Porosity Concrete etc is nowadays gaining more popularity in storm water management. Pervious concrete paving blocks are permeable blocks that provide runoff control while serving as the wearing course for low-traffic volume roads, parking lots, walkbike pathways and other applications like residential roads, alleys and driveways, shoulders medians, under overpasses bridges. Application of pervious concrete includes mainly groundwater purifier, heat reducer and sound absorber.This paper is an intended preliminary study on the characteristics and application of Pervious Concrete Paver Blocks.